STUDI PERENCANAAN SISTEM UNTUK PENDUKUNG KEPUTUSAN PROYEK KAPAL BANGUNAN BARU - Suyadi Suyadi (Diponegoro University, 2009)
Since Presidential decree No 5 2005 on the empowerment of the Indonesian shipping industry applies, theIndonesian shipbuilding industry has officially gained support from the Indonesian government to be able tocompete in the national as well as international market. Along with the globalization era and a lot ofshipbuilding orders, the shipyard management has to do some improvement to the shipyard to be morecompetitive. One of efforts that should be done is by improving the management of incoming orders. This isvery important to do because during this time the shipyard management has to collect a lot of informationfrom departments in the shipyard manually to consider accepted shipbuilding orders.In this paper, a new model to manage new shipbuilding orders is developed. The model is implementedwithin a computer-based decision support system that is related to an existing system of production, planningand control in the shipyard. The approach used in the development of this system is ROMC (Representation,Operation, Memory Aids and Control Mechanism).The aim of the developed decision support system is to assist all decision makers in defining problems,developing alternative solution; , and chosing various alternative decisions in the system development thereare three steps to be done : (i) building data base, (ii) building model base, and (iii) building dialogue base